Aid grants vs. technical cooperation grants: Implications for inclusive growth in sub-Saharan Africa, 1984-2018 - Simplice Asongu; Hillary Chijindu Ezeaku (African Governance and Development Institute (AGDI), 2020)
This study investigates the effects of aid grants on inclusive growth in 37 Sub-Saharan African countries for the period 1984-2018. Grant aid is decomposed into aid grants and technical cooperation grants. Two inclusive growth indicators are used namely: gross domestic product (GDP) per capita growth and unemployment rate. The dynamic panel autoregressive distributed lag (ARDL) approach which is employed comprises three different estimators; the pooled mean group (PMG), mean group (MG), and dynamic fixed effect (DFE). The Hausman diagnostics were used to assess the efficiency and consistency of the estimators. Based on the PMG estimator, our findings show that aid grants and technical cooperation grants exert a positive influence on GDP per capita growth in the long-run. However, while the observed influence of aid grants is found to be significant, technical cooperation grants display insignificant effects. In the short run, however, the PMG estimates show that aid grants and technical cooperation grants have negative and insignificant effects on GDP per capita growth. On the other hand, results based the DFE estimators reveal that neither of the aid grants has influenced the unemployment rate positively in the short-run. However, whereas aid grants contribute significantly to the reduction of the unemployment rate in the long run, technical cooperation grants do not. This study complements the attendant literature by assessing how aid grants versus technical cooperation grants affect inclusive growth. The findings are relevant to international policy coordination for the attainment of sustainable development goals.
Keywords: B20; F35; F50; O10; O55; 330; Aid grants; Technical Cooperation grants; Inclusive growth